Linear Integral Equations Theory & Technique - Kanwal, Ram P. (Modern Birkhäuser Classics,, 2013)
Many physical problems that are usually solved by differential equation methods can be solved more effectively by integral equation methods. Such problems abound in applied mathematics, theoretical mechanics, and mathematical physics. This uncorrected softcover reprint of the second edition places the emphasis on applications and presents a variety of techniques with extensive examples. Originally published in 1971, Linear Integral Equations is ideal as a text for a beginning graduate level course. Its treatment of boundary value problems also makes the book useful to researchers in many applied fields.